PERENCANAAN MANAJEMEN KONSTRUKSI PADA BANGUNAN GEDUNG ASRAMA MAHASISWI KABUPATEN LANDAK 4 LANTAI DI JALAN UJUNG PANDANG 1 KOTA PONTIANAK: PERENCANAAN MANAJEMEN KONSTRUKSI PADA BANGUNAN GEDUNG ASRAMA MAHASISWI KABUPATEN LANDAK 4 LANTAI DI JALAN UJUNG PANDANG 1 KOTA PONTIANAK - Okta Hardiani, Annisa Nurul; Iffananda, La Resha; Asmadi, ASMADI; ryanti, Eva (Jurusan Teknik Sipil Polnep, 2024)
Construction infrastructure development in West Kalimantan Province is carried out every year in order to achieve community welfare. One example is building a hostel building. Dormitory is a building that is used to accommodate students from within or outside the area. To fulfill the facilities and amenities for Landak Regency female students, it is necessary to build a dormitory carried out by the Landak Regency Government. Construction management is the right solution in planning a dormitory building. The data collected included primary data in the form of field observations (land area) and field documentation (photos) and secondary data in the form of working drawings, basic prices for 2022 Pontianak City, AHSP based on PUPR Government Regulations 2022 and literature in the form of books and e-books. There are 5 aspects of construction management that will be discussed, namely project cost management, project quality management, project time management, project human resource management (HR) and project occupational safety and health (K3) management. Obtain volume calculations, budget plan (RAB), recapitulation of RAB, work plans and requirements (RKS), S curve, Network Planning using the CPM method, workforce requirements, identification of OHS risks, risk control hierarchy and RK3K costs. The results of the planning have obtained a budget plan of Rp. 10.301.793.000,00, the planned duration of time for work to be completed is 210 calendar days or 7 months based on the S curve, project quality uses general requirements based on planned drawing specification data, human resources get manpower requirements the most workers were 78 people and got the APD and APK requirements and calculated the cost of the contract work safety and health plan (RK3K) of IDR 33. 867.000,00. Keywords: student dormitory, planning, construction management.